Emotional experiences of women who access early pregnancy assessment units: a qualitative investigation - Sergio A. Silverio; Maria Memtsa; Geraldine Barrett; Venetia Goodhart; Judith Stephenson; Davor Jurković; Jennifer A. Hall (Taylor & Francis Group, 2022)
Purpose: Early pregnancy complications are common and often result in pregnancy loss, which can be emotionally challenging for women. Research on the emotional experiences of those attending Early Pregnancy Assessment Units [EPAUs] is scarce. This analysis explored the emotions which women spontaneously reported when being interviewed about their experiences of using EPAU services. Materials and methods: Semi-structured telephone interviews were conducted with a purposive sample of 38 women. Using Thematic Framework Analysis, we identified six unique emotional typologies which mapped onto women's clinical journeys. Results: Women with ongoing pregnancies were characterized as having: "Anxious Presentation" or "Sustained Anxiety due to Diagnostic Uncertainty", dependent on whether their initial scan result was inconclusive. Women with pregnancy loss had one of four emotional typologies, varying by diagnostic timing and required interventions: "Anxious-Upset"; "Anxious-Upset after Diagnostic Uncertainty"; "Anxious-Upset with Procedural Uncertainty"; "Anxious with Sustained Uncertainty". Conclusions: We provide insights into the distinct emotions associated with different clinical pathways through EPAU services. Our findings could be used to facilitate wider recognition of women's emotional journeys through early pregnancy complications and stimulate research into how best to support women and their partners, in these difficult times.